The Impact of Providing Chatbot Content on Developing the English Communication Skills Among Al-Azhar Kindergarten Teachers - Ahmed Tawfik, Ghada Mohamed; Elnagar, Mohamed Elsayed; Alazab, Gehan Sedky (European Scientific Journal, ESJ, 2023)
This paper focuses on investigating the impact of using Chatbot content on improving the English communication skills of Al-Azhar Al-Sharif kindergarten teachers. The researcher used a quasi-experimental design to explain the differences that occurred in the teachers` performance before and after the intervention of the Chatbot content. This design required the researcher to develop a performance observation checklist, which is the main tool of this research. In addition, the researcher constructed the Chatbot content and the e-training programme. After the research design was completed, thirty-three (33) female Azhari kindergarten teachers participated in this experiment. The performance observation checklist was used for evaluating the teachers` performance before and after the intervention of the Chatbot content and for measuring the teachers` retention of the acquired skills. At the end of the research, a statistical analysis of the results was applied. The results showed a statistically significant difference at the level of 0.05 on the performance observation checklist`s mean scores of the sample teachers’ pre-and post-application of the Chatbot content in favour of the postapplication. The second statistical analysis of the performance observation checklist showed that there is no significant difference between the sample teachers` mean scores in the post- and follow-up application of the Chatbot content. These results are proof that validate the research`s main assumption that Chatbot content can improve the English communication skills of kindergarten teachers.